IMPROVING FINANCIAL AND CREDIT MECHANISMS FOR THE DEVELOPMENT OF SMALL BUSINESS ENTITIES (American Journal of Interdisciplinary Research and Development, 2023)
This article considers ways to improve the financial and credit mechanism for the development of small businesses. The purpose of this study is to develop scientific proposals and practical recommendations for improving the financial and credit mechanism for the development of small businesses in a modern market economy. During the study, the following methods were used: grouping, comparison, scientific thinking, economic-statistical, empirical evaluation, correlation-regression analysis, forecasting of research objects and presentation of results. An “active action model” of the taxation mechanism has been created in order to increase the economic activity of small businesses and ensure their efficient operation.